2000
DOI: 10.1890/1051-0761(2000)010[1047:eohdob]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Human Development on Bacteriological Water Quality in Coastal Watersheds

Abstract: Human development along the land-seawater interface is considered to have significant environmental consequences. Development can also pose an increased human health risk. In a rapidly developing coastal region we investigated this phenomenon throughout a series of five estuarine watersheds, each of which differed in both the amount and type of anthropogenic development. Over a four-year period we analyzed the abundance and distribution of the enteric pathogen indicator microbes, fecal coliform bacteria and Es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
180
3
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 353 publications
(203 citation statements)
references
References 23 publications
18
180
3
2
Order By: Relevance
“…In urban areas, the combination of extensive impervious surface cover and high density of storm drains promote the rapid flushing of bacteria from lawns, roads, and other surfaces into streams (Frenzel & Couvillion, 2002;Mallin et al, 2000). However, we have documented high concentrations of E. coli and total coliforms under baseflow, rather than storm flow, conditions.…”
Section: Urban Land Cover and Bacterial Abundancementioning
confidence: 66%
See 3 more Smart Citations
“…In urban areas, the combination of extensive impervious surface cover and high density of storm drains promote the rapid flushing of bacteria from lawns, roads, and other surfaces into streams (Frenzel & Couvillion, 2002;Mallin et al, 2000). However, we have documented high concentrations of E. coli and total coliforms under baseflow, rather than storm flow, conditions.…”
Section: Urban Land Cover and Bacterial Abundancementioning
confidence: 66%
“…For example, Frenzel and Couvillion (2002) found that concentrations of E. coli, fecal coliforms, and enterococci were higher in stream sub-basins with higher human population densities in and near Anchorage, Alaska. Similarly, Mallin, Williams, Esham, and Lowe (2000) found that fecal coliform abundance correlated positively with human population density, percentage of developed land, and percentage of impervious surface in five tidal creek basins in North Carolina.…”
Section: Urban Land Cover and Bacterial Abundancementioning
confidence: 85%
See 2 more Smart Citations
“…Liebezeit and Wostmann (2010) stated that the most dominant fecal contamination in the water of the Siak River in Pekanbaru was caused by the large population. Mallin et al, (2000) explained that the abundance of fecal coliform significantly correlated with the number of inhabitants in the basin, and even highly correlated with the percentage of land area developed in the watershed.…”
Section: Total Coliform Oil and Fatmentioning
confidence: 96%